Comparative analysis of two flow decomposition approaches and their applications in diagnosing water vapor in extreme precipitation events over Xinjiang province, China - Cao, Jie; Ma, Shuping; Ran, Lingkun (Frontiers in Earth Science, 2022)
Water vapor flux divergence under the terrain-following coordinate system is decomposed into slow and fast manifolds with the adoption of Barnes filter method and the synoptic approach based on Helmholtz theorem in this study. The performances and applications of both methods are evaluated in precipitating events over Xinjiang province in China when traditional analysis fails to capture the evolutions of extreme precipitations caused by multi-scale systems and complicated terrains. A blizzard with a short duration under weak moisture environments and a persistent torrential rainfall event with abundant water vapor in summer are selected as test examples for comparative analysis of the relationships between water vapor divergence and precipitation characteristics with the adoptions of both traditional synoptic diagnosis and two decomposition methods. It is found that divergent areas of the total water vapor flux divergence at middle and high levels are blocked by false convergence at low levels as the precipitation weakens in both cases, which leads to the failure of traditional synoptic diagnoses. Meanwhile, the two decomposition methods can provide superior indicators for extreme precipitation, especially before rainfall decreases or terminates. The synoptic approach performs better than the Barnes filter method as the latter sharply decreases accuracy as the complexity of flow fields and moisture conditions increase. Remedies for relieving this problem are proposed before its being used for further applications.